Pydsbuilder – A Dataset Builder Written in Python Django - BERCIU, Liviu-Marian (Studia Universitatis Babeș-Bolyai Informatica, 2025)
Data mining and the analysis of open-source projects have become crucial in recent research, driven by the vast availability of data across multiple programming domains. This paper focuses on two main objectives: first, to present an experience report for designing a software quality data mining tool, and secondly, to provide an open-source solution, PyDs, that facilitates the creation of datasets specifically aimed at analyzing software quality attributes. PyDs, leveraging Python and the Django Framework, provides a comprehensive solution for researchers, encompassing data extraction from repositories, the application of software analysis tools, and the consolidation of results into a coherent format conducive to in-depth experimentation and analysis. This tool addresses the pressing need for effective data mining capabilities in evaluating software quality, allowing the research community to harness the full potential of the vast resources offered by open-source software projects. Received by editors: 13 September 2024 2010 Mathematics Subject Classification. 68N99. 1998 CR Categories and Descriptors. D2.0 [Software Engineering]: General – Standards; D2.9 [Software Engineering]: Management – Software Quality Assurance